Induction of hair growth in hair follicle cells and organ cultures upon treatment with 30 kHz frequency inaudible sound via cell proliferation and antiapoptotic effects. Issue 3 (2022) - CHOI‑, HYANGTAE; LEE, YONGHEE; SHIN, SEUNG HYUN; NAM, JIN; PARK, WON‑SEOK; PARK, BYUNG CHEOL; KIM, BEOM JOON
No abstract available